The Efficacy and Mechanism of Chinese Herbal Medicine on Diabetic Kidney Disease - Zhenzhen Lu; Yifei Zhong; Wangyi Liu; Ling Xiang; Yueyi Deng (Journal of Diabetes Research)
Diabetic kidney disease (DKD) is the most common microvascular complication of diabetes and is one of the main causes of end-stage renal disease (ESRD) in many countries. The pathological features of DKD are the hypertrophy of mesangial cells, apoptosis of podocytes, glomerular basement membrane (GBM) thickening, accumulation of extracellular matrix (ECM), glomerular sclerosis, and tubulointerstitial fibrosis. The etiology of DKD is very complicated and many factors are involved, such as genetic factors, hyperglycemia, hypertension, hyperlipidemia, abnormalities of renal hemodynamics, and metabolism of vasoactive substances. Although some achievements have been made in the exploration of the pathogenesis of DKD, the currently available clinical treatment methods are still not completely effective in preventing the progress of DKD to ESRD. CHM composed of natural products has traditionally been used for symptom relief, which may offer new insights into therapeutic development of DKD. We will summarize the progress of Chinese herbal medicine (CHM) in the treatment of DKD from two aspects. In clinical trials, the Chinese herbal formulas were efficacy and safety confirmed by the randomized controlled trials. In terms of experimental research, studies provided evidence for the efficacy of CHM from the perspectives of balancing metabolic disorders, reducing inflammatory response and oxidative stress, antifibrosis, protecting renal innate cells, and regulating microRNA and metabolism. CHM consisting of different ingredients may play a role in synergistic interactions and multiple target points in the treatment of DKD.